Muscle carnitine availability plays a central role in regulating fuel metabolism in the rodent - Porter, Craig; Constantin-Teodosiu, Dumitru; Constantin, Despina; Leighton, Brendan; Poucher, Simon M.; Greenhaff, Paul L. (Wiley, 2017)
The body carnitine pool is primarily confined to skeletal muscle, where it regulates carbohydrate (CHO) and fat usage. Mildronate (3-(2,2,2-trimethylhydrazinium)-propionate) inhibits carnitine synthesis and tissue uptake, but the impact of carnitine depletion on whole-body fuel selection, muscle fuel metabolism and its molecular regulation is under-investigated. Male lean Zucker rats received water (control, n=8) or mildronate-supplemented water (mildronate, n=8) for 10 days (1.6 g.kg-1 body mass (bm).day-1 day 1-2, 0.8 g.kg-1 bm.day-1 thereafter). From day 7-10, animals were housed in indirect calorimetry chambers after which soleus muscle and liver were harvested. Food and fluid intake, weight gain and physical activity levels were similar between groups from day 7-10. Compared to control, mildronate depleted muscle total carnitine (P<0.001) and all carnitine esters. Furthermore, whole-body fat oxidation was less (P<0.001) and CHO oxidation was greater (P<0.05) compared to control, whilst soleus and liver glycogen content were less (P<0.01 and P<0.01, respectively).